The clinical significance of cognitive reappraisal and expressive suppression across positive and negative emotions: evidence on the Polish version of the Emotion Regulation Questionnaire – Positive/Negative (ERQ-PN) - Paweł Larionow; Paweł Larionow; Jarosław Ocalewski; Karolina Mudło-Głagolska; Maciej Michalak; Monika Mazur (Frontiers in Psychiatry)
In line with the contemporary shift towards assessing emotion-based constructs across positive and negative emotions, this study presents an investigation on the clinical relevance of assessing two broadly studied emotion regulation strategies, cognitive reappraisal and expressive suppression, across positive and negative emotions. More specifically, the study aimed (1) to examine psychometric properties of a first Polish version of the Emotion Regulation Questionnaire – Positive/Negative (ERQ-PN), and (2) to investigate whether, where and why the assessment of emotional valence (positive vs negative) is needed for a more nuanced understanding of two emotion regulation processes. The sample comprised 391 Polish adults aged 18–73, who filled out the ERQ-PN, and a series of short self-report questionnaires on anxiety and depression symptoms, well-being, and emotion regulation difficulties. The Polish ERQ-PN has demonstrated strong psychometric properties, including the intended four-factor structure, which was invariant across females and males. Using a series of various analyses, we have found empirical support for the importance of distinguishing emotional valence in the examined emotion regulation strategies. Among the four strategies, cognitive reappraisal of negative emotions has emerged as the most clinically relevant, showing strong associations with better mental health outcomes. Theoretically, these findings support the process model of emotion regulation, demonstrating that various emotion regulation strategies have specific links with mental health outcomes, with these links being more or less pronounced depending on the emotional valence. Given its strong psychometric properties and high clinical relevance, the ERQ-PN is a good measure of emotion regulation strategies across positive and negative emotions.